A Building a Foundation for Health: A Review of Healthy Lifestyle Knowledge Among Indonesian Cleaning Workers in the Malaysian Cleaning Services Industry - Fitri, Mustika; Fitriana, Lisna Anisa; Sulastri, Afianti (International Journal of Health Sciences, 2024)
Introduction: The global economy is affected by Indonesian migrant workers' destinations in Malaysia, Taiwan, Hong Kong, and Singapore. Poor housing and cleanliness make it hard for Indonesian workers, especially cleaning service workers, to stay healthy. Employees in the cleaning service business may not understand how to manage their health or navigate the healthcare system due to health literacy issues. Indonesian workers in Malaysia are assessed for workplace health literacy and empowerment. Addressing these issues and improving health literacy can enhance public health, eliminate health inequities, and empower people to make health decisions. Methods: The cross-sectional accidental sampling study involves 23 Indonesian workers from a prominent Malaysian university. All Indonesian workers were given a full explanation of the 15-question healthy living questionnaire. Results: 47.9% of migrant workers had sufficient knowledge, 39.1% had poor knowledge, and 13% had good knowledge. Conclusion: Poor personal hygiene affects Indonesian workers in Malaysia, focusing on workplace health knowledge and empowerment. It stresses health literacy, especially for the poor. To improve public health, reduce health inequities, and empower people to make health decisions, these concerns and health literacy initiatives are crucial.